Strategy and the entrepreneur: various viewpoints for analysis - Osorio Tinoco, Fabián; Gálvez Albarracín, Edgar; Murillo Vargas, Guillermo (Cuadernos de Administración, 2010)
Research in the field of entrepreneurship comes from diverse disciplines, and in this regard the Strategy and the Entrepreneur are two concepts requiring inspection. In this paper the authors offer from the perspective of the Strategy a context for the analysis of the actor known as an entrepreneur. The first part of the document discusses the configuration and construction of the field of the strategy domain. The second part develops the concept of the entrepreneur, from the perspective of the individual, the process, the organization and environment (Gartner, 1985), and the third part deals, from different perspectives, with the relationship between strategy and entrepreneurship, such perspectives include: strategy as a plan and its putting into action, strategy as a projection of its leadership and strategy as an approach to environment.